ANALISIS PROSES PEMBELAJARAN MATEMATIKA BERBASIS DARING MENGGUNAKAN APLIKASI GOOGLE CLASSROOM PADA MASA PANDEMI COVID-19 (Jurnal PGSD, 2020)
The purpose of this research describe the analysis of the learning process of mathematics online based using the google classroom application in IVB grade at elementary school Aisyiyah, Sukabumi City. This study used descriptive qualitative method. Data collection techniques using interviews and documentation. The writer acts as an instrument for collecting data. Data analysis techniques using the analysis model according to Miles and Huberman which consists of data reduction, data display and conclusion drawing/verificication. The subjects of this study were students of class IV B in the academic year 2019/2020. The number of students is 20 people. The results showed that the google classroom application can help and facilitate teachers and students in implementing the distance learning process. Based on the results of the study it can be concluded that online learning using the google classroom application proved effective carried out during the WFH consequence covid-19 pandemic. Utilization of Google classroom is acceptable and further developed even though it still requires revamping the availability of supporting resources. Keywords: learning process, google classroom, math